A "caixa preta" do cuidado: relações de gênero e histórias de vida de trabalhadoras técnicas de enfermagem - Erica Dumont Pena (2012)
The object of this work is the relations of care for the other, analyzed through the life stories of two women, current nursing techniques workers. The concept of care, taken by the feminist studies point of view, understood as a social relation whose object is the other, constitutes the central axis of the analyzes. Understanding the relations of care are composed by actions and emotions, experienced by agents in a various contexts of which they are part, we find to unveil them in these life stories, focusing on the family sphere and on the sphere of work in the Health Center. To construct the life histories, we used narrative interviews. Another methodological procedure adopted was a participant observation in the interviews situations and also, daily in the health center, for a period of three months. In the first chapter, we situate the contemporary discussion of care, located in the feminist studies. In it, we present the construction of the object and also the methodological options for the understanding it. In the second chapter, we focus in the story of Lucy and Rose in the family purposing of gath and analyze the memories of the care and some meanings constructed by them about their daily practices of care in this sphere. In the third chapter, we emphasize their practices and discourses concerning the work in the health care and its socialmeaning. In these chapters, we highlight the consubstantiality of the social relations of care, gender and social class in dialogue with the feminist perspective of care and take the concept of gender as a central category. The results revealed that the relations of care surpass the instrumental goals of survival and professional techniques, revealing the symbolic context, which also stands for violence and anger, attitudes that are not being evidencieted in some studies in this area.